(untitled) - Dieken, Connie (Hoboken, 2013)
Presents advice for improving personal influence by becoming, and being seen as being, the "real deal," or a person with the genuine leadership qualities of inner presence, verbal presence, and outer presence.
Keywords: Leadership,Lãnh đạo